Influence of Cavity Design on Calcium Hydroxide Removal from Root Canal Irregularities - Selen Küçükkaya Eren; Emel Uzunoğlu Özyürek (Cumhuriyet University, 2019)
Objective: Conservative endodontic cavity (CEC) design has recently developed to maintain the stability of tooth and provided an alternative to traditional endodontic cavity (TEC) design. The purpose of this study was to assess the influence of cavity design on calcium hydroxide (Ca(OH)2) removal from artificial grooves in the coronal and apical parts of root canals. Materials and Methods: Fourty extracted human mandibular premolars with single canals were randomly assigned to CEC or TEC groups (n=20). Following cavity preparation, the root canals were instrumented and then, each tooth was sectioned longitudinally. Two standardized grooves were prepared in the coronal and apical parts of 1 root half. Ca(OH)2 was placed into the grooves and the root halves reassembled. After 1 week, each root canal was enlarged to a final apical size of 40 and irrigation was performed with the sonic activation of 2.5% sodium hypochlorite and 17% ethylenediaminetetraacetic acid solutions. The remaining Ca(OH)2 in the grooves was evaluated using a stereomicroscope and the images were scored by 2 examiners. Data were analyzed using the Mann-Whitney U and Wilcoxon tests. Ca(OH)2 remnants were found in both groups. Results: There was no significant difference between the CEC and TEC groups in terms of Ca(OH)2 removal efficacy (p>0.05). The grooves in the coronal and apical parts of the roots presented similar amount of Ca(OH)2 remnantsin both groups (p>0.05). Conclusion: The cavity design had no effect on the removal of Ca(OH)2 from root canal irregularities.